6x+83=9x-7

Simple and best practice solution for 6x+83=9x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+83=9x-7 equation:


Simplifying
6x + 83 = 9x + -7

Reorder the terms:
83 + 6x = 9x + -7

Reorder the terms:
83 + 6x = -7 + 9x

Solving
83 + 6x = -7 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
83 + 6x + -9x = -7 + 9x + -9x

Combine like terms: 6x + -9x = -3x
83 + -3x = -7 + 9x + -9x

Combine like terms: 9x + -9x = 0
83 + -3x = -7 + 0
83 + -3x = -7

Add '-83' to each side of the equation.
83 + -83 + -3x = -7 + -83

Combine like terms: 83 + -83 = 0
0 + -3x = -7 + -83
-3x = -7 + -83

Combine like terms: -7 + -83 = -90
-3x = -90

Divide each side by '-3'.
x = 30

Simplifying
x = 30

See similar equations:

| 2x^3-x^2-1=0 | | 2+45-3/2=12b | | 8t-5=19 | | 6x-11-7x+12= | | 4x^2-4x+4=0 | | -x^2+x-12=0 | | 4(y+3)=7-5y | | (19x-17)-(3x-72)=-13+(13x+83) | | 9-9x=84-44x | | (1x)(6x)+7x+12=0 | | 6x+2=5(x+1) | | 80-2x=4x-14 | | (6x)(6x)+7x+12=0 | | 6x-(8x-10)=87-(21+10x) | | 8n-25=39 | | 6x+26=14-46 | | 8z-6=11z-7 | | 6-8x=58-22x | | 3x+13=-11-9x | | -10=2x-5 | | 136-4x=41x+21 | | 2y^2+7y-4=0 | | 4x+7=-5x+1 | | 9n+2=22 | | 92-2x=4x+8 | | 8x+3=4(2x+3) | | 7n+5=39 | | 4n+3=25 | | 9n+6=21 | | H^2-11h+30=0 | | 5-6z=6z-5 | | 7x+19=12x-1 |

Equations solver categories